Analysis of Strategy Strengthening Based on Managerial Accounting as a Determining Factor of the Sustainability of Digital Business Models - Dina Nadiyah Faiqoh; Harto Harto; Lulut Ismaya (Asian Journal of Management Analytics, 2026)
Factors influencing profitability need to be studied more deeply so that companies can increase profits sustainably. Research using quantitative data from the financial reports of the consumer goods and trading sector on the Indonesia Stock Exchange in 2024 shows mixed results: TCID is strong although capital efficiency can still be improved, KOBX is high risk with good debt management, UNTR is efficient, ECII needs to focus on profitability, MAPI and MIDI are healthy but MAPI needs to maintain profits, RALS is highly liquid but cautious, RANC is moderately high risk, and SONA is in very healthy condition for expansion. Facing domestic and global competition, all issuers in this sector need to strengthen their competitiveness through product innovation, supply chain efficiency, and the use of digital technology in management and marketing.